Pengaruh Penerapan Gaya Mengajar Inklusi Terhadap Keterampilan Gerak Dasar Pada Servis Atas Dalam Permainan Bola Voli Peserta Didik Kelas XI SMA Negeri 1 Tondano - Gerald Rendialdi Malino; Eduard E. Kumenap; Yuliana Sattu (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Physical education is a very important subject in school, because physical education learning has the concept of developing psychomotor, cognitive and affective aspects. Physical education has a learning process that prioritizes basic movements rather than basic techniques, but good and correct mastery of basic movements can make it easier for students to master basic techniques. The problem in this research is whether the implementation of an inclusive teaching style has an influence on the basic movement skills of the top serve in volleyball in class XI students at SMA Negeri 1 Tondano. This research aims to find out how much influence the inclusive teaching style has on basic movement skills in volleyball serves in class XI students at SMA Negeri 1 Tondano. The research method used is an experimental research method. The population in this study was all students in class XI of SMA Negeri 1 Tondano, totaling 212 students. The SMAple in this study was 20 people taken at random and then divided into 2 groups, namely the experimental group, which consisted of 10 students, and the control group, which consisted of 10 students. This group division was carried out using the Simple Random Sampling Technique. The research instrument used was "Basic movement test on top serves in volleyball". Based on hypothesis testing using t test statistics, this research can be concluded that there is an influence of the application of an inclusive teaching style on basic movement skills in the top serve in the volleyball game of class XI students at SMA Negeri 1 Tondano.